A Companion to Anticlassicisms in the Cinquecento (De Gruyter, 2023)
'Anticlassicisms' react to the various forms of 'classicisms.' This volume discusses the history and possible implications of the label in Renaissance studies and analyzes such 'anticlassicisms.' It distinguishes the various forms of opposition to 'classicisms' as to their scope (on a scale between radical poetological dissension to merely sectorial opposition in a given literary genre) and to their alternative models, be they authors or texts.